The Development of Prosocial Attention Across Two Cultures - Hepach, Robert; Herrmann, Esther (Frontiers in Psychology, 2019)
Despite the significance of prosocial attention for understanding variability in children’s prosociality little is known about its expression beyond infancy and outside the Western cultural context. In the current study we asked whether children’s sensitivity to others’ needs varies across ages and between a Western and Non-Western cultural group. We carried out a cross-cultural and cross-sectional eye tracking study in Kenya (n = 129) and Germany (n = 84) with children between the ages of 3 to 9 years old. Half the children were presented with videos depicting an instrumental helping situation in which one adult reached for an object while a second adult resolved or did not resolve the need. The second half of children watched perceptually controlled non-social control videos in which objects moved without any adults present. German children looked longer at the videos than Kenyan children who in turn looked longer at the non-social compared to the social videos. At the same time, children in both cultures and across all age groups anticipated the relevant solution to the instrumental problem in the social but not in the non-social control condition. We did not find systematic changes in children’s pupil dilation in response to seeing the problem occur or in response to the resolution of the situation. These findings suggest that children’s anticipation of how others’ needs are best resolved is a cross-cultural phenomenon that persists throughout childhood.